2007
DOI: 10.1111/j.1574-6968.2007.00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional expression of the mitochondrial alternative oxidase ofAspergillus fumigatusand its induction by oxidative stress

Abstract: Aspergillus fumigatus possesses a branched mitochondrial electron transport chain, with both cyanide-sensitive and -insensitive oxygen-consumption activities. Mitochondrial reactive oxygen species mediate signaling for alternative oxidase (AOX) expression. A 1173 bp-long Afaox gene encoding a 40 kDa protein has been cloned and identified. Recombinant constructs containing the Afaox ORF were transformed into Escherichia coli and Saccharomyces cerevisiae for heterologous expression. In A. fumigatus, AOX activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 39 publications
1
50
0
5
Order By: Relevance
“…heterologous expression systems. The AOX of the plant Sauromatum guttatum Schott (voodoo lily) is able to confer CN-resistant respiration in isolated mitochondria in the yeast Schizosaccharomyces pombe and the AOXs of the fungi Pichia (Hansenula) anomala and Aspergillus fumigatus are functional when expressed in S. cerevisiae (Crichton et al 2005;Mathy et al 2006;Magnani et al 2007). The AOX of the tunicate animal Ciona intestinalis has been shown to be functional when expressed in cultured human cells (Hakkaart et al 2006).…”
Section: Secondary Endosymbiosismentioning
confidence: 99%
See 3 more Smart Citations
“…heterologous expression systems. The AOX of the plant Sauromatum guttatum Schott (voodoo lily) is able to confer CN-resistant respiration in isolated mitochondria in the yeast Schizosaccharomyces pombe and the AOXs of the fungi Pichia (Hansenula) anomala and Aspergillus fumigatus are functional when expressed in S. cerevisiae (Crichton et al 2005;Mathy et al 2006;Magnani et al 2007). The AOX of the tunicate animal Ciona intestinalis has been shown to be functional when expressed in cultured human cells (Hakkaart et al 2006).…”
Section: Secondary Endosymbiosismentioning
confidence: 99%
“…Fasting in the amoeba Chaos carolinensis also increases oxidative stress and the activation of AOX is seen as a protective mechanism (Deng et al 2002). In A. fumigatus AOX mRNA expression is induced by paraquat and menadione, two compounds that lead to cellular oxidative stress (Magnani et al 2007). AOX activation in durum wheat mitochondria also led to a decrease in the rate of superoxide anion generation (Pastore et al 2001).…”
Section: Control Of Reactive Oxygen Species Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of two ROS-generating agents, paraquat and H 2 O 2 were investigated in 12 fungal species, the results of which indicated exposure of fungal spores or mycelia to both agents stimulated CRR (Angelova et al 2005). In A. fumigatus, AOX activity and mRNA expression were both induced with menadione or paraquat, suggesting an important role of AOX under oxidative stress conditions (Magnani et al 2007). A recent study by our group showed that oxidative stress in batch cultures of A. niger caused by over-oxygenation led to a general decrease of ATP content in the cells (Li et al 2008b) which corroborates the engagement of alternative respiration under such conditions proposed by Bai et al (2003b).…”
Section: The Role Of Aox In Oxidative Stressmentioning
confidence: 99%